Peran Ilmuwan Muslim dalam Kemajuan Ilmu-Ilmu Keislaman pada Masa Dinasti Mamluk di Mesir - Stiawan, Randi (Local History & Heritage, 2023)
This article aims to examine the progress of knowledge under the Mamluk Dynasty, utilizing a historical methodology involving heuristic, source criticism, interpretation, and historiography stages. The research adopts a literature-based approach, conducting library research and collecting data from various sources related to the theme. Several factors drove the growth of Islamic knowledge during this period, with Mamluk leaders prioritizing education, as reflected in the establishment of numerous educational institutions. Additionally, collaborations with external entities, including economic relations with Europe, further propelled this advancement. Contributions from Muslim intellectuals, such as Ibn Khaldun and Al-Suyuti, strengthened educational institutions. The results of this research indicate that the Mamluk Dynasty played a significant role in the advancement of Islamic knowledge during that era. In conclusion, this article underscores the substantial impact of the Mamluk Dynasty on the development of Islamic knowledge and the emphasis on education as the foundation of Islamic civilization in the region.